2012
DOI: 10.1371/journal.pone.0048140
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide SNP Discovery from Transcriptome of Four Common Carp Strains

Abstract: BackgroundSingle nucleotide polymorphisms (SNPs) have been used as genetic marker for genome-wide association studies in many species. Gene-associated SNPs could offer sufficient coverage in trait related research and further more could themselves be causative SNPs for traits. Common carp (Cyprinus carpio) is one of the most important aquaculture species in the world accounting for nearly 14% of freshwater aquaculture production. There are various strains of common carp with different economic traits, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 36 publications
1
46
0
3
Order By: Relevance
“…With the help of the SNP calling module in CLC Genomics Workbench (CLC bio, Aarhus, Denmark), as well as a SNP quality screening procedure, they identified 342,104 intra-specific SNPs for channel catfish, 366,269 intraspecific SNPs for blue catfish, and 420,727 inter-specific SNPs between channel catfish and blue catfish; these SNPs were found to be distributed within 16,562 unique genes in channel catfish and 17,423 unique genes in blue catfish. In another study, RNA-seq was performed to discover geneassociated SNPs in four strains of common carp (Cyprinus carpio) (Xu et al, 2012). BWA and SAMtools software were applied to align the reads to reference transcriptome and call SNPs, and, in total, 712,042 intra-strain SNPs and 53,893 inter-SNPs were identified.…”
Section: Snp Discoverymentioning
confidence: 99%
“…With the help of the SNP calling module in CLC Genomics Workbench (CLC bio, Aarhus, Denmark), as well as a SNP quality screening procedure, they identified 342,104 intra-specific SNPs for channel catfish, 366,269 intraspecific SNPs for blue catfish, and 420,727 inter-specific SNPs between channel catfish and blue catfish; these SNPs were found to be distributed within 16,562 unique genes in channel catfish and 17,423 unique genes in blue catfish. In another study, RNA-seq was performed to discover geneassociated SNPs in four strains of common carp (Cyprinus carpio) (Xu et al, 2012). BWA and SAMtools software were applied to align the reads to reference transcriptome and call SNPs, and, in total, 712,042 intra-strain SNPs and 53,893 inter-SNPs were identified.…”
Section: Snp Discoverymentioning
confidence: 99%
“…In addition, it is also considered an alternative vertebrate fish model to zebrafish (Danio rerio). A variety of C. carpio genome resources have been developed over the past decade, including a large number of genetic markers 8,9 , genetic maps [10][11][12][13] , a BAC-based physical map 14,15 , a large number of ESTs [16][17][18] and cDNA microarrays 19 . Recently, a comparative exomic study of C. carpio and D. rerio has been reported, providing additional genome resourcing data for the research community 20 .…”
mentioning
confidence: 99%
“…The validation rate was 18.32% (37/202). Xu et al (2012) performed Transcriptome sequencing of four strains of common carp with Solexa HiSeq2000 platform. Validation of selected SNPs with Sanger sequencing revealed that 48% percent of SNPs (12 of 25) were tested to be true SNPs.…”
Section: Resultsmentioning
confidence: 99%
“…The developed transcriptome single nucleotide polymorphism (SNP) markers by 454 pyrosequencing technology have been applied in the breeding of blunt snout bream (Megalobrama amblycephala), and visible resources of fish transcriptome data have great potential in the field of breeding (Gao et al, 2012). The applications of developed and validated expressed sequence tag (EST)-derived SNP markers have been reported in aquatic species such as European hake (Milano et al, 2011), salmonids (Seeb et al, 2011;Lemay et al, 2013), Atlantic herring (Clupea harengus) (Helyar et al, 2012), rainbow trout (Boussaha et al, 2012;Salem et al, 2012), common carp (Xu et al, 2012), and turbot (Scophthalmus maximus) (Vera et al, 2013). However, very little is known about the development and validation of EST-derived SNP markers in O. potamophila.…”
Section: Introductionmentioning
confidence: 99%